The Wihkohtowin: Ritual Feasting among Cree and Métis Peoples in Northern Alberta - Westman, Clinton N. (Anthropologica, 2015)
I provide new data and interpretations on the wihkohtowin, a key ritual feast of Cree and Métis peoples in northern Alberta. I draw on my own interviews and ethnographic research, archived interviews, other archival data and published accounts of the wihkohtowin. As a historically important shamanic ritual practised in the contemporary context, the wihkohtowin is relevant to relations with animals and non-human nature, including spirits and the dead, as well as relations within human society. Taking an approach adapted from Don Handelman and my informants, I suggest that the wihkohtowin merits deeper analysis in its own right: historically, linguistically, phenomenologically and emotionally.